Inducible isoforms of cyclooxygenase and nitric-oxide synthase in inflammation. - Vane, J R (1994)
Cyclooxygenase (COX) converts arachidonic acid to prostaglandin H2, which is further metabolized to prostanoids. Two isoforms of COX exist: a constitutive (COX-1) and an inducible (COX-2) enzyme. Nitric oxide is derived from L-arginine by isoforms of nitric-oxide synthase (NOS; EC 1.14.13.39): constitutive (cNOS; calcium-dependent) and inducible (iNOS; calcium-independent). Here we have investigated inducible isoforms of COX and NOS in the acute, chronic, and resolving stages of a murine air pouch model of granulomatous inflammation. COX and NOS activities were measured in skin samples in the acute phase, up to 24 h. Activities in granulomatous tissue were measured at 3, 5, 7, 14, and 21 days for the chronic and resolving stages of inflammation. COX-1 and COX-2 proteins were assessed by Western blot. COX activity in the skin increased over the first 24 h and continued to rise up to day 14. COX-2 protein rose progressively, also peaking at day 14. COX-1 protein remained unaltered throughout. The iNOS activity increased over the first 24 h in the skin, with a further major increase in the granulomatous tissue between days 3 and 7, followed by a decrease at day 14 and a further increase at day 21. The rise in COX and NOS activities in the skin during the acute phase reinforces the proinflammatory role for prostanoids and suggests one also for nitric oxide. However, in the chronic and resolving stages, a dissociation of COX and NOS activity occurred. Thus, there may be differential regulation of these enzymes, perhaps due to the changing pattern of cytokines during the inflammatory response.